Ultrahigh-nickel polycrystalline composite ternary positive electrode material as well as preparation method and application thereof

Through high-temperature composite with MXene material and the coating treatment of cobalt hydroxide and FAS, the problems of easy cracking and excessive residual alkali of ultra-high nickel ternary cathode material are solved, and the stability and electrochemical properties of the material are achieved. promote.

CN119495736APending Publication Date: 2025-02-21SHAANXI IRICO NEW MATERIAL CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411729097.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Ultra-high nickel ternary cathode material is prone to cracking during charging and discharging, resulting in a decline in battery performance. During the preparation process, the volatility of lithium and excessive lithium react with air, resulting in excessive residual alkali.

Method used

The MXene material with a two-dimensional structure is used to recombine high-temperature nickel ternary positive electrode material to form a tight interface structure to reduce the cracking of secondary spherical particles, and pass cobalt hydroxide and trimethoxy groups (1H,1H,2H,2H -The cladding of -heptafluorodecyl)silane FAS reduces residual alkali and improves water resistance.

Benefits of technology

It improves the stability and electrochemical properties of the material, reduces the cracking and residual alkali content of the material, enhances water resistance, and thus improves the overall performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an ultrahigh-nickel polycrystalline composite ternary positive electrode material as well as a preparation method and application thereof, and belongs to the technical field of lithium batteries. The ultrahigh-nickel polycrystalline composite ternary positive electrode material comprises a modified material, the modified material is a sintered product prepared from an ultrahigh-nickel polycrystalline ternary positive electrode material precursor subjected to oxidation sintering treatment, a lithium source and an MXene material, and the modified material is sequentially coated with cobaltous hydroxide and a coating agent trimethoxy (1H, 1H, 2H, 2H)-1, 2, 3, 4-tetramethyl-1, 3-pentanediol monoisobutyrate. And the water-resistant layer is formed by (2H, 2H-heptadecafluorodecyl) silane. According to the ultrahigh-nickel ternary positive electrode material provided by the invention, the MXene material is directly combined with the ternary positive electrode material at a high temperature to form a tight interface structure, so that the structural stability of secondary spherical particles is enhanced, cracks are reduced, and the stability and electrochemical performance of the material are improved; the cobalt hydroxide and the water-resistant material trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane are used for coating, so that the contact between the material and H2O and CO2 in the air is reduced, the residual alkali is reduced, and the production and storage of the material are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and specifically relates to an ultra-high nickel polycrystalline composite ternary positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have been commercialized based on their advantages such as high energy density, wide operating temperature range, and long cycle life. With the rapid development of the electric vehicle market and the pursuit of long driving range, the demand for high energy density batteries has increased dramatically. Among them, ultra-high nickel ternary cathode materials have attracted much attention due to their higher energy density and low cobalt, environmental friendliness, and low cost compared to low nickel or medium-low nickel materials.

[0003] However, due to the high nickel content, ultra-high nickel materials are affected by their inherent physical and chemical performance defects and cannot fully meet the needs of electric vehicles. First, during the charging and discharging process, the repeated extraction and embedding of lithium ions will cause the internal particles to expand and shrink in volume, generate large internal stress, and thus cause the material to crack. These cracks will destroy the contact between the primary particles and expose new interfaces. The electrolyte will penetrate into the secondary particles from the cracks and react with the exposed surface to produce by-products and gases, causing the cracks to increase, the battery materials to pulverize, and the battery impedance to increase, resulting in the electrical performance of the positive electrode material to decline to failure. Second, in the preparation of ultra-high nickel ternary positive electrode materials, lithium will volatilize at high temperatures. Therefore, in order to synthesize ordered layered compounds, an excessive amount of lithium source will be added during the sintering process. Although the cation mixing can be suppressed to a certain extent, the excessive lithium will react with H2O and CO2 in the air on the surface of the material, resulting in excessive residual alkali. The above problems will be aggravated with the increase of nickel content. In order to better meet the high performance requirements of lithium-ion batteries, improve the problems of easy cracking and high residual alkali of ultra-high nickel ternary positive electrode materials, and at the same time improve their electrochemical properties, it is of great significance to develop an ultra-high nickel polycrystalline ternary positive electrode material with good material stability and excellent electrochemical properties. Summary of the invention

[0004] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide an ultra-high nickel polycrystalline composite ternary positive electrode material and a preparation method and application thereof. The material has a certain water resistance while avoiding the cracking of secondary spherical particles and reducing residual alkali. In addition, the method is a method for preparing an ultra-high nickel polycrystalline ternary positive electrode material that can improve the cracking of secondary spherical particles and excessive residual alkali. A MXene material with a two-dimensional structure is used to perform high-temperature composite with an ultra-high nickel ternary positive electrode material by solid-phase sintering to obtain a modified material to improve the problem of easy cracking of its secondary spherical particles. The modified material is sequentially coated with cobaltous hydroxide and trimethoxysilane (trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane FAS), which gives a hydrophobic layer to the surface of the material while reducing the residual alkali, thereby improving the defect of easy water absorption of the high nickel ternary positive electrode material.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing an ultra-high nickel polycrystalline composite ternary positive electrode material, comprising the following steps: S1: The ultra-high nickel polycrystalline ternary cathode material precursor, lithium source and MXene material are mixed evenly, and then oxidatively sintered to obtain a primary sintered product; S2: mixing the primary sintered product with cobaltous hydroxide, and performing secondary sintering after the mixing is completed to obtain a secondary sintered product; S3: dissolving the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane in a solvent to prepare a coating solution; S4: Immerse the secondary sintered product in a coating liquid, and use spray drying to evenly coat the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane on the secondary sintered product to obtain an ultra-high nickel polycrystalline composite ternary positive electrode material.

[0006] In one embodiment, in S1, the ultra-high nickel polycrystalline ternary positive electrode material precursor is nickel cobalt manganese hydroxide NixCoyMnz(OH)2, wherein x≥0.9, 0≤y≤0.1, 0≤z≤0.1, and x+y+z=1.

[0007] In one embodiment, in S1, the lithium source is lithium hydroxide; the MXene material includes a transition metal carbide or a transition metal carbonitride, wherein the transition metal is one of Ti, Zr, W, Nb, Ta, V, and Fe.

[0008] In one embodiment, in S1, the molar ratio of the ultra-high nickel polycrystalline ternary positive electrode material precursor to the lithium source is 1:(1.03-1.09), and the mass ratio of the ultra-high nickel polycrystalline ternary positive electrode material precursor to the MXene material is 1:(0.01%-0.1%).

[0009] In one embodiment, in S1, the oxidation sintering is performed in an atmosphere sintering furnace, the atmosphere of the oxidation sintering is air or oxygen, the sintering temperature is 700-800°C, the heating rate is 1-10°C / min, and the holding time is 5-15h.

[0010] In one embodiment, in S2, the amount of cobaltous hydroxide added is 1%-10% of the primary sintered mass.

[0011] In one embodiment, in S2, the secondary sintering is carried out in an atmosphere sintering furnace, the atmosphere of the secondary sintering is air or oxygen, the sintering temperature is 500-700°C, the heating rate is 1-10°C / min, and the insulation time is 5-15h; in S3, the solvent is a methanol solution, and the volume ratio of the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane to the solvent is 1:100.

[0012] In one embodiment, in S4, the temperature of immersing the secondary sintered sample into the coating liquid is 50-100° C., and the immersion time is 20-50 min.

[0013] The present invention also provides an ultra-high nickel polycrystalline composite ternary positive electrode material prepared according to the preparation method of the ultra-high nickel polycrystalline composite ternary positive electrode material, wherein the ultra-high nickel polycrystalline composite ternary positive electrode material includes a modified material, wherein the modified material is a sintered product prepared from an ultra-high nickel polycrystalline ternary positive electrode material precursor, a lithium source and a MXene material after oxidation sintering treatment, and the outside of the modified material is sequentially coated with cobaltous hydroxide and a water-resistant layer formed by a coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane.

[0014] The present invention also provides a lithium battery, comprising the ultra-high nickel polycrystalline composite ternary positive electrode material.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing an ultra-high nickel polycrystalline composite ternary positive electrode material. The method uses a MXene material with a two-dimensional structure to obtain a modified material by high-temperature composite with an ultra-high nickel ternary positive electrode material through solid-phase sintering, so that the MXene material and the positive electrode material are directly combined under a high temperature environment to form a tight interface structure. This in-situ synthesis method can enhance the stability of the lattice, alleviate the volume change stress caused by the escape and embedding of lithium ions, reduce the cracking of secondary spherical particles, and improve the stability and electrochemical properties of the composite material. At the same time, the MXene material has good thermal stability and flame retardancy, and has certain benefits for the safety of lithium-ion batteries. In addition, cobaltous hydroxide and a water-resistant material (coating agent trimethoxy(1H,1H,2H,2H-heptadecafluorodecyl)silane FAS) are used as coating layers to act on the surface of the ultra-high nickel ternary positive electrode material. Cobaltous hydroxide can reduce the high residual alkali caused by excessive lithium source on the surface, and the water-resistant material FAS coating layer forms a water-resistant layer on the surface of the obtained target product, reducing the influence of moisture in the air on the material surface, thereby improving the electrochemical performance while improving the stability of the material. DETAILED DESCRIPTION

[0016] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0017] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0018] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0019] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0020] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0021] The present invention provides an ultra-high nickel polycrystalline composite ternary positive electrode material and a preparation method and application thereof.

[0022] The present invention provides a method for preparing an ultra-high nickel polycrystalline composite ternary positive electrode material, comprising the following steps: (1) After the ultra-high nickel polycrystalline ternary cathode material precursor, lithium source and MXene material are fully mixed in a ball mill, oxidation sintering is performed in an atmosphere furnace to obtain a primary sintered product; (2) mixing the primary sintered product obtained in step (1) with cobaltous hydroxide, and after the mixing is completed, performing secondary sintering in an atmosphere sintering furnace to obtain a secondary sintered product; (3) fully dissolving the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane (FAS) in a solvent to form a coating solution; (4) Immersing the secondary sintered product obtained in step (2) in the coating solution of step (3) at a certain temperature for a certain period of time, and using spray drying to uniformly coat the FAS on the secondary sintered product to obtain the target product, an ultra-high nickel polycrystalline composite ternary positive electrode material.

[0023] Wherein, the precursor in step (1) is nickel cobalt manganese hydroxide NixCoyMnz(OH)2, wherein x≥0.9, 0≤y≤0.1, 0≤z≤0.1, and x+y+z=1.

[0024] Wherein, the lithium source in step (1) is lithium hydroxide; the MXene material includes transition metal carbide or transition metal carbonitride, wherein the transition metal is one of Ti, Zr, W, Nb, Ta, V, and Fe.

[0025] Wherein, in step (1), the precursor and the lithium source are mixed in a molar ratio of 1:1.03-1.09, and the precursor and the MXene material are mixed in a mass ratio of 1:0.01%-0.1%.

[0026] In step (1), the ultra-high nickel polycrystalline ternary cathode material precursor, the lithium source and the MXene material are mixed by ball milling, the mass ratio of material to ball in the ball milling is 1:0.6, and the mixing time is 0.5-2h.

[0027] Wherein, the atmosphere of the sintering furnace in step (1) is air or oxygen, the sintering temperature is 700-800°C, the heating rate is 1-10°C / min, and the holding time is 5-15h.

[0028] Wherein, the amount of cobaltous hydroxide added in step (2) is 1%-10% of the quality of the primary sintered product.

[0029] Wherein, in step (2), the atmosphere of the sintering furnace is air or oxygen, the sintering temperature is 500-700° C., the heating rate is 1-10° C. / min, and the holding time is 5-15h.

[0030] Wherein, the solvent in step (3) is a methanol solution, and the volume ratio of the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane to the solvent is 1:100.

[0031] Wherein, in step (4), the temperature of immersing the secondary sintered sample into the coating liquid is 50-100° C., and the immersion time is 20-50 min.

[0032] On the other hand, the present invention also provides an ultra-high nickel polycrystalline composite ternary positive electrode material, including a modified material, wherein the modified material is a sintered product made of an ultra-high nickel polycrystalline ternary positive electrode material precursor, a lithium source and a MXene material after oxidation sintering treatment, and the exterior of the modified material is sequentially coated with a water-resistant layer formed by cobaltous hydroxide and a coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane.

[0033] The ultra-high nickel polycrystalline composite ternary cathode material provided by the present invention directly combines the MXene material with the ternary cathode material at high temperature to form a tight interface structure, enhance the structural stability of the secondary spherical particles, reduce cracking, and improve the stability and electrochemical performance of the material; and utilizes cobaltous hydroxide and the water-resistant material trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane for coating to reduce the contact of the material with H2O and CO2 in the air, reduce residual alkali and facilitate the production and storage of the material.

[0034] The present invention also provides an application of the ultra-high nickel polycrystalline composite ternary positive electrode material prepared by the above preparation method in a lithium battery.

[0035] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0036] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0037] Example 1 (1) Ni0.9Co0.05Mn0.05(OH)2 and LiOH·H2O were mixed at a molar ratio of 1:1.06 and a mass ratio of 1:0.05% with MXene material. The mass ratio of the total weight of the material to the mass of the ball was 1:0.6. The mixture was mixed on a ball mill for 1 h. After being fully mixed, the material was sieved through a 100-mesh sieve and placed in a crucible. In an oxygen atmosphere, the heating rate was 5°C / min, the sintering temperature was 750°C, the holding time was 12 h, and after sintering, the material was sieved through a 400-mesh sieve to obtain a primary sintered product. (2) mixing the primary sintered product obtained in step (1) with 3% cobaltous hydroxide in a ball mill for 1 hour. After mixing, the product was heated at a rate of 5°C / min in an oxygen atmosphere, the sintering temperature was 600°C, and the holding time was 10 hours. After sintering, the product was sieved through a 400-mesh sieve to obtain a secondary sintered product. (3) the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane (FAS) and the methanol solution are fully mixed at a volume ratio of 1:100 to form a coating solution; (4) The secondary sintered sample obtained in step (2) is added into the coating solution of step (3), immersed at 70° C. for 20 min, and FAS is uniformly coated on the secondary sintered product by spray drying to obtain the target product A.

[0038] Example 2 (1) Ni0.9Co0.05Mn0.05(OH)2 and LiOH·H2O were mixed at a molar ratio of 1:1.06 and a mass ratio of 1:0.07% with MXene material. The total weight of the material and the mass ratio of the small balls were 1:0.6. The mixture was mixed on a ball mill for 1 h. After being fully mixed, the material was sieved through a 100-mesh sieve and placed in a crucible. In an oxygen atmosphere, the heating rate was 5°C / min, the sintering temperature was 750°C, and the holding time was 12 h. After sintering, the material was sieved through a 400-mesh sieve to obtain a primary sintered product. (2) mixing the primary sintered product obtained in step (1) with 2.5% of cobaltous hydroxide in a ball mill for 1 hour. After mixing, the product was heated at a rate of 5°C / min, sintered at 600°C, and kept at this temperature for 10 hours in an oxygen atmosphere. After sintering, the product was sieved through a 400-mesh sieve to obtain a secondary sintered product. (3) the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane (FAS) and the methanol solution are fully mixed at a volume ratio of 1:100 to form a coating solution; (4) The secondary sintered sample obtained in step (2) is added into the coating solution of step (3), immersed in the solution at 70° C. for 30 min, and the FAS is evenly coated on the secondary sintered product by spray drying to obtain the target product B.

[0039] Example 3 (1) Ni0.9Co0.05Mn0.05(OH)2 and LiOH·H2O were mixed at a molar ratio of 1:1.06 and a mass ratio of 1:0.01% with MXene material. The total weight of the material and the mass ratio of the small balls were 1:0.6. The mixture was mixed on a ball mill for 1 h. After being fully mixed, the material was sieved through a 100-mesh sieve and placed in a crucible. In an oxygen atmosphere, the heating rate was 5°C / min, the sintering temperature was 750°C, the holding time was 12 h, and after sintering, the material was sieved through a 400-mesh sieve to obtain a primary sintered product. (2) mixing the primary sintered product obtained in step (1) with 1% cobaltous hydroxide in a ball mill for 1 hour. After mixing, the product was heated at a rate of 5°C / min, sintered at 600°C, and kept at this temperature for 10 hours in an oxygen atmosphere. After sintering, the product was sieved through a 400-mesh sieve to obtain a secondary sintered product. (3) the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane (FAS) and the methanol solution are fully mixed at a volume ratio of 1:100 to form a coating solution; (4) The secondary sintered sample obtained in step (2) is added into the coating solution of step (3), immersed at 70° C. for 20 min, and FAS is uniformly coated on the secondary sintered product by spray drying to obtain the target product C.

[0040] Example 4 (1) Ni0.9Co0.05Mn0.05(OH)2 and LiOH·H2O were mixed at a molar ratio of 1:1.06 and a mass ratio of 1:0.1% with MXene material. The total weight of the material and the mass ratio of the ball were 1:0.6. The mixture was mixed on a ball mill for 1 h. After being fully mixed, the material was sieved through a 100-mesh sieve and placed in a crucible. In an oxygen atmosphere, the heating rate was 5°C / min, the sintering temperature was 750°C, and the holding time was 12 h. After sintering, the material was sieved through a 400-mesh sieve to obtain a primary sintered product. (2) mixing the primary sintered product obtained in step (1) with 10% of cobaltous hydroxide in a ball mill for 1 hour. After mixing, the product was heated at a rate of 5°C / min, sintered at 600°C, and kept at this temperature for 10 hours in an oxygen atmosphere. After sintering, the product was sieved through a 400-mesh sieve to obtain a secondary sintered product. (3) the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane (FAS) and the methanol solution are fully mixed at a volume ratio of 1:100 to form a coating solution; (4) The secondary sintered sample obtained in step (2) is added into the coating solution of step (3), immersed in the solution at 70° C. for 50 min, and the FAS is evenly coated on the secondary sintered product by spray drying to obtain the target product D.

[0041] Example 5 (1) Ni0.9Co0.05Mn0.05(OH)2 and LiOH·H2O were mixed at a molar ratio of 1: 1.03 and a mass ratio of 1:0.01% with MXene material. The mass ratio of the total weight of the material to the mass of the ball was 1:0.6. The material was mixed on a ball mill for 0.5 h. After being fully mixed, the material was sieved through a 100-mesh sieve and placed in a crucible. In an air atmosphere, the heating rate was 1°C / min, the sintering temperature was 700°C, the holding time was 5 h, and after sintering, the material was sieved through a 400-mesh sieve to obtain a primary sintered product. (2) mixing the primary sintered product obtained in step (1) with 1% cobaltous hydroxide on a ball mill for 1 hour. After mixing, the product was heated at a rate of 1°C / min, sintered at 500°C, and kept at this temperature for 5 hours in an air atmosphere. After sintering, the product was sieved through a 400-mesh sieve to obtain a secondary sintered product. (3) the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane (FAS) and the methanol solution are fully mixed at a volume ratio of 1:100 to form a coating solution; (4) The secondary sintered sample obtained in step (2) is added into the coating solution of step (3), immersed in the solution at 50° C. for 20 min, and the FAS is evenly coated on the secondary sintered product by spray drying to obtain the target product E.

[0042] Example 6 (1) Ni0.9Co0.05Mn0.05(OH)2 and LiOH·H2O were mixed at a molar ratio of 1: 1.09 and a mass ratio of 1:0.1% with MXene material. The total weight of the material and the mass ratio of the small balls were 1:0.6. The mixture was mixed on a ball mill for 2 h. After being fully mixed, the material was passed through a 100-mesh sieve and placed in a crucible. In an oxygen atmosphere, the heating rate was 10°C / min, the sintering temperature was 800°C, and the holding time was 15 h. After sintering, the material was passed through a 400-mesh sieve to obtain a primary sintered product. (2) mixing the primary sintered product obtained in step (1) with 10% of cobaltous hydroxide in a ball mill for 1 hour. After mixing, the product was heated at a rate of 10°C / min, sintered at 700°C, and kept at this temperature for 15 hours in an air atmosphere. After sintering, the product was sieved through a 400-mesh sieve to obtain a secondary sintered product. (3) the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane (FAS) and the methanol solution are fully mixed at a volume ratio of 1:100 to form a coating solution; (4) The secondary sintered sample obtained in step (2) is added into the coating solution of step (3), immersed in the solution at 70° C. for 50 min, and the FAS is evenly coated on the secondary sintered product by spray drying to obtain the target product F.

[0043] Comparative Example 1 (1) Ni0.9Co0.05Mn0.05(OH)2 and LiOH·H2O were mixed in a ball mill at a molar ratio of 1:1.06 and a mass ratio of the total weight of the materials to the mass of the balls of 1:0.6 for 1 hour. After being fully mixed, the materials were sieved through a 100-mesh sieve and placed in a crucible. In an oxygen atmosphere, the heating rate was 5°C / min, the sintering temperature was 750°C, and the holding time was 12 hours. After the sintering was completed, the materials were sieved through a 400-mesh sieve to obtain a primary sintered product; (2) mixing the primary sintered product obtained in step (1) with 3% cobaltous hydroxide in a ball mill for 1 hour. After mixing, the product was heated at a rate of 5°C / min in an oxygen atmosphere, the sintering temperature was 600°C, and the holding time was 10 hours. After sintering, the product was sieved through a 400-mesh sieve to obtain a secondary sintered product. (3) the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane (FAS) and the methanol solution are fully mixed at a volume ratio of 1:100 to form a coating solution; (4) The secondary sintered sample obtained in step (2) is added into the coating solution of step (3), immersed in the solution at 70° C. for 20 min, and the FAS is evenly coated on the secondary sintered product by spray drying to obtain the target product G.

[0044] Comparative Example 2 (1) Ni0.9Co0.05Mn0.05(OH)2 and LiOH·H2O were mixed at a molar ratio of 1:1.06 and a mass ratio of 1:0.05% with MXene material. The mass ratio of the total weight of the material to the mass of the ball was 1:0.6. The mixture was mixed on a ball mill for 1 h. After being fully mixed, the material was sieved through a 100-mesh sieve and placed in a crucible. In an oxygen atmosphere, the heating rate was 5°C / min, the sintering temperature was 750°C, the holding time was 12 h, and after sintering, the material was sieved through a 400-mesh sieve to obtain a primary sintered product. (2) the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane (FAS) and the methanol solution are fully mixed in a volume ratio of 1:100 to form a coating solution; (3) The primary sintered sample obtained in step (1) is added into the coating solution of step (2), immersed in the solution at 70° C. for 20 min, and the FAS is evenly coated on the secondary sintered product by spray drying to obtain the target product H.

[0045] Comparative Example 3 (1) Ni0.9Co0.05Mn0.05(OH)2 and LiOH·H2O were mixed at a molar ratio of 1:1.06 and a mass ratio of 1:0.05% with MXene material. The mass ratio of the total weight of the material to the mass of the ball was 1:0.6. The mixture was mixed on a ball mill for 1 h. After being fully mixed, the material was sieved through a 100-mesh sieve and placed in a crucible. In an oxygen atmosphere, the heating rate was 5°C / min, the sintering temperature was 750°C, the holding time was 12 h, and after sintering, the material was sieved through a 400-mesh sieve to obtain a primary sintered product. (2) The primary sintered product obtained in step (1) was mixed with 3% of cobaltous hydroxide in a ball mill for 1 hour. After mixing, the mixture was heated at a rate of 5°C / min in an oxygen atmosphere, the sintering temperature was 600°C, and the holding time was 10 hours. After sintering, the mixture was sieved through a 400-mesh sieve to obtain the target product I.

[0046] Table 1 shows the residual alkali in powder of samples of comparative examples 1-3 and samples of embodiments 1-6. The moisture content is the value measured by weight method after the samples were placed in the same environment for 24 hours. Table 2 shows the withholding capacity and first efficiency at 4.3V of samples of comparative examples 1-3 and samples of embodiments 1-6, as well as the capacity retention rate after 50 cycles of 1C at 4.5V.

[0047] Table 1. Residual alkali and water content of comparative examples and examples

[0048] Table 2. Capacity and cycle data of comparative examples and examples

[0049] The above results show that the electrochemical properties of the sample can be improved after modification of the MXene material. Cobaltous hydroxide has a reducing effect on the residual alkali of the sample and at the same time has a certain improvement on the electrochemical performance of the sample; FAS coating makes the material have a certain water resistance, reduces the reaction of the sample with moisture in the environment, and improves the stability of the material.

[0050] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing an ultra-high nickel polycrystalline composite ternary positive electrode material, characterized in that: The following steps are involved: S1: The ultra-high nickel polycrystalline ternary cathode material precursor, lithium source and MXene material are mixed evenly, and then oxidatively sintered to obtain a primary sintered product; S2: mixing the primary sintered product with cobaltous hydroxide, and performing secondary sintering after the mixing is completed to obtain a secondary sintered product; S3: dissolving the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane in a solvent to prepare a coating solution; S4: Immerse the secondary sintered product in a coating liquid, and use spray drying to evenly coat the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane on the secondary sintered product to obtain an ultra-high nickel polycrystalline composite ternary positive electrode material.

2. The method for preparing the ultra-high nickel polycrystalline composite ternary positive electrode material according to claim 1, characterized in that: In S1, the ultra-high nickel polycrystalline ternary positive electrode material precursor is nickel cobalt manganese hydroxide NixCoyMnz(OH)2, wherein x≥0.9, 0≤y≤0.1, 0≤z≤0.1, and x+y+z=1.

3. The method for preparing the ultra-high nickel polycrystalline composite ternary positive electrode material according to claim 1, characterized in that: In S1, the lithium source is lithium hydroxide; the MXene material includes a transition metal carbide or a transition metal carbonitride, wherein the transition metal is one of Ti, Zr, W, Nb, Ta, V, and Fe.

4. The method for preparing the ultra-high nickel polycrystalline composite ternary positive electrode material according to claim 1, characterized in that: In S1, the molar ratio of the ultra-high nickel polycrystalline ternary positive electrode material precursor to the lithium source is 1:(1.03-1.09), and the mass ratio of the ultra-high nickel polycrystalline ternary positive electrode material precursor to the MXene material is 1:(0.01%-0.1%).

5. The method for preparing the ultra-high nickel polycrystalline composite ternary positive electrode material according to claim 1, characterized in that: In S1, the oxidation sintering is performed in an atmosphere sintering furnace, the atmosphere of the oxidation sintering is air or oxygen, the sintering temperature is 700-800°C, the heating rate is 1-10°C / min, and the holding time is 5-15h.

6. The method for preparing the ultra-high nickel polycrystalline composite ternary positive electrode material according to claim 1, characterized in that: In S2, the added amount of cobaltous hydroxide is 1%-10% of the primary sintered mass.

7. The method for preparing the ultra-high nickel polycrystalline composite ternary positive electrode material according to claim 1, characterized in that: In S2, the secondary sintering is carried out in an atmosphere sintering furnace, the atmosphere of the secondary sintering is air or oxygen, the sintering temperature is 500-700°C, the heating rate is 1-10°C / min, and the insulation time is 5-15h; in S3, the solvent is a methanol solution, and the volume ratio of the coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane to the solvent is 1:

100.

8. The method for preparing the ultra-high nickel polycrystalline composite ternary positive electrode material according to claim 1, characterized in that: In the above S4, the temperature of the secondary sintered sample immersed in the coating liquid is 50-100° C., and the immersion time is 20-50 min.

9. An ultra-high nickel polycrystalline composite ternary positive electrode material prepared according to the method for preparing an ultra-high nickel polycrystalline composite ternary positive electrode material according to any one of claims 1 to 8, characterized in that: The ultra-high nickel polycrystalline composite ternary positive electrode material includes a modified material, which is a sintered product made from an ultra-high nickel polycrystalline ternary positive electrode material precursor, a lithium source and a MXene material after oxidation sintering treatment. The outside of the modified material is sequentially coated with a water-resistant layer formed by cobaltous hydroxide and a coating agent trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane.

10. A lithium battery, characterized in that: Including the ultra-high nickel polycrystalline composite ternary positive electrode material as described in claim 9.

Citation Information

Cited By

  • Composite ternary positive electrode material and preparation method and application thereof

    CN120300168A

  • Modified high-nickel ternary positive electrode material, preparation method thereof, positive electrode sheet and lithium ion battery

    CN122868517A